Crown–rump length measurement: a new age for first‐trimester ultrasound?. (1st September 2021) - Stirnemann, J.; Massoud, M.; Fries, N.; Dumont, C.; Haddad, G.; Bessis, R.; Dhombres, F.; Salomon, L. J.
Abstract : Linked article: This Editorial comments on the article by Gadsbøll et al. Click here to view the article.